Pathomorphological and immunohistochemical evaluation of chronic (isolated) organ tuberculosis in a cow - ULUSOY, Yavuz; KILINÇ, Bahadır; PİR, Halil; TERZİ, Funda; DUDAKLI, Orhan (Etlik Veteriner Mikrobiyoloji Dergisi, 2022)
We aimed to reveal the case pathomorphological and immunohistochemically. General findings of chronic isolated organ tuberculosis in cattle in the late period are presented in this report. In the history of the case, the 2-year-old cattle died as a result of respiratory distress and was brought to the pathology laboratory to determine the cause of death. In necropsy, it was detected that encapsulated caseous foci localized in the caudal lobe of the right lung and mediastinal lymph nodes were inactive. Histopathologically, non-mineralized, secondary caseous necrosis, peripheral mononuclear cell infiltration, and fibrous capsule were detected. Immunohistologically, some macrophages and neutrophils were found to be positive for Mycobacterium bovis. However, regional lymph nodes were negative. Also, there was no histopathological reaction in other parenchymatous organs. As a result, the postprimary form of tuberculosis is not always detectable when compared to other forms. Therefore, we believe that this case report may be useful. Keywords: Cow, chronic organ tuberculosis, immunological detection, pathomorphology.
Keywords: 3. Good health